METHODS OF ENSURING NATIONAL SECURITY OF CENTRAL ASIAN COUNTRIES UNDER NEW GEOPOLITICAL CONDITIONS - RYAZANTSEV, Sergey; AKMALOVA, Munira; KARIMOV, Mirzokosim; VAZIROV, Zafar (CENTRAL ASIA AND THE CAUCASUS, 2018)
Vital interests of the Shanghai Five are concentrated in the post-Soviet countries, including Central Asia. The article substantiates the need to work out an SCO foreign policy strategy in regard to the post-Soviet space, which is based on national interests. A conclusion is made that national interests and a specific strategy in regard to the post-Soviet space need to be recorded in the SCO doctrinal documents. National interests of the Central Asian countries are based on permanent, rather than immediate, applied or institutional goals. The article also examines certain problems and peculiarities of religious extremism, and religious terrorism as its extreme form. Special attention is heeded to the formulation of characteristic features of a partnership as a special and independent format of international relations. In conclusion, the author points to the manifestation of global tendencies in regard to state sovereignty and security as the research aim.